2021
DOI: 10.1021/acs.analchem.1c01017
|View full text |Cite
|
Sign up to set email alerts
|

To Love and to Kill: Accurate and Selective Colorimetry for Both Chloride and Mercury Ions Regulated by Electro-Synthesized Oxidase-like SnTe Nanobelts

Abstract: Herein, SnTe nanobelts (NBs) with efficient oxidase–mimetic activity were synthesized by the simple electrochemical exfoliation method. A specific inhibition effect of Cl– on the enzymatic behavior of the pure SnTe NBs was discovered, which was accordingly used for establishing a highly feasible, sensitive, selective, and stable Cl– colorimetric assay. The detection concentration range was 50 nM to 1 mM, and the lowest detection limit was 20 nM for Cl–. In addition, a signal on-off-on route based on the SnTe N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…For example, the formation of either the stable thymine complex (T-Hg 2+ -T) or amalgams with noble metals, can reverse the inhibitory effect that certain molecules or nanoparticles have on the oxidase mimetic activity of specific nanostructures. In the presence of Hg­(II) ions, the oxidase-like activity of the indicated nanostructures is restored and the concentration of the oxidation product increases. , …”
Section: Chemical Sensors For Mercury Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the formation of either the stable thymine complex (T-Hg 2+ -T) or amalgams with noble metals, can reverse the inhibitory effect that certain molecules or nanoparticles have on the oxidase mimetic activity of specific nanostructures. In the presence of Hg­(II) ions, the oxidase-like activity of the indicated nanostructures is restored and the concentration of the oxidation product increases. , …”
Section: Chemical Sensors For Mercury Ionsmentioning
confidence: 99%
“…In the presence of Hg(II) ions, the oxidase-like activity of the indicated nanostructures is restored and the concentration of the oxidation product increases. 28 , 29 …”
Section: Chemical Sensors For Mercury Ionsmentioning
confidence: 99%
“…Nanozyme-based analytical chemistry is a paramount toolkit for the rational design of biosensors for the application of environmental monitoring, clinical diagnosis, and food analysis. Although tremendous research interest has been devoted to exploring nanozyme-based biosensors, such as immunosensors and aptasensors, the sensing modes and catalytic performance to achieve the desired biosensing of analytes is challenging. The main nanozyme-catalyzed reaction members, including substrates, nanozymes, and catalytic products, can act as sensing modes because they can be responsive to external stimuli (small molecules, proteins, ions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…After the addition of mercury salt into the Ag aerogel system, significantly promoted oxidase-like activity is achieved due to the formation of silver amalgams. 25 Interestingly, the catalytic property for oxidase mimicking is strongly correlated with the concentration of the introduced Hg 2+ , and it is surprising that the obtained Hg/Ag shows an extraordinary catalytic activity and excellent SERS enhancement when ultralow Hg 2+ concentration is used. It can be concluded that such remarkably enhanced catalytic activity for oxidase mimicking can be the result of the formation of Hg SACs, which has been proved by the results of high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) and X-ray photoelectron spectroscopy (XPS) measurements.…”
Section: ■ Introductionmentioning
confidence: 99%